2004
DOI: 10.1590/s1516-14392004000200019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high sintering pressure on the microhardness and wear resistance of diamond powder and silicon carbide-based composites

Abstract: The work reported on here involved the development of several samples of "diamond-SiC" composite produced under sintering pressures of up to 9.0 GPa at temperatures of up to 1973 7K. The average size of the diamond micropowder crystals used was 40/28 µm. The sintering process was carried out in a 2500-ton hydraulic press equipped with an anvil-type high-pressure device having a toroidal work surface and a central concavity diameter of 20 mm. The microhardness and wear resistance of the samples were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However, when the starting material consist of smaller submicron size diamond crystals, successful sintering by the infiltration method usually is limited to composites less than 2 mm thick [2]. In this case of sintering the microhardness reached a maximum value of 52 ± 3 GPa for 23.5 wt.% of SiC in compact [3]. Another method is HT-HP sintering of diamond and SiC powders mixture.…”
Section: Inroductionmentioning
confidence: 99%
“…However, when the starting material consist of smaller submicron size diamond crystals, successful sintering by the infiltration method usually is limited to composites less than 2 mm thick [2]. In this case of sintering the microhardness reached a maximum value of 52 ± 3 GPa for 23.5 wt.% of SiC in compact [3]. Another method is HT-HP sintering of diamond and SiC powders mixture.…”
Section: Inroductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] However, these studies mainly focused on the effect of the hardness of the same material on wear resistance, such as WC-Co cemented carbide, "diamond-SiC" composite, and polycrystalline cubic boron nitride (PcBN), among others. 3,4,11,12 To date, there is limited research exploring the wear resistance of different materials under identical hardness conditions. This limitation is primarily due to the inherent hardness of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also established a positive correlation between the hardness and wear resistance of various materials such as steel, cemented carbide, ceramics, and superhard materials 1–11 . However, these studies mainly focused on the effect of the hardness of the same material on wear resistance, such as WC‐Co cemented carbide, “diamond‐SiC” composite, and polycrystalline cubic boron nitride (PcBN), among others 3,4,11,12 . To date, there is limited research exploring the wear resistance of different materials under identical hardness conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although these traditional tool bit cermets have for decades been extensively used, there is currently an increasing demand for new tool bit materials [1,6]. Among the novel developments in this area, nanostructured materials are modern alternatives for improvement industrial tools [8]. Technical results reported in the literature [1][2][3][4][5][6][7][8][9], have demonstrated that polycrystalline diamond crystals (PDC) and polycrystalline boron cubic nitride (PcBN) sintered compacts exhibit superior properties when fabricated from nanopowders at high pressure and high temperature (HPHT) conditions.…”
Section: Introductionmentioning
confidence: 99%